PENGARUH LATIHAN KECEPATAN REAKSI TERHADAP KECEPATAN TENDANGAN SABIT PADA ATLET PENCAK SILAT PERGURUAN EMPAT BANDING BUDI TUNGGUL HITAM KOTA PADANG - Muhammad Fariq Riyandi; Jeki Haryanto; Roma Irawan; Juanda Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the lack of speed in the crescent kicks of athletes from the Empat Banding Budi Tunggul Hitam school, which results in low athletic performance and slow kicking speeds. The objective of this study is to determine the effect of reaction speed training on crescent kick speed among these athletes. The study employed a One-Group Pretest-Posttest Design. The population consisted of 68 athletes (35 male and 33 female). Purposive sampling was used to select a sample of 20 male and female athletes. The research instrument used was a crescent kick speed test. Data analysis techniques included prerequisite tests (normality and homogeneity tests) and hypothesis testing. The results indicate that reaction speed training influenced crescent kick speed among the athletes. The sample achieved an average score of 20.05 on the pre-test and 26.85 on the post-test; this increase in the mean score by 6.8 demonstrates the effectiveness of the intervention. This finding is statistically significant, as the t-test yielded a Sig. (2-tailed) value of 0.000. According to t-test decision criteria, if the significance value is less than 0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Since 0.000 < 0.05, it is concluded that there is a statistically highly significant difference between the average pre-test and post-test scores. Therefore, the study concludes that the implemented reaction speed training can improve the crescent kick speed of athletes at the Empat Banding Budi Tunggul Hitam school in Padang City.